The Influence of Psychological Tests and Student Commute Distance on Student Learning Outcomes - Siti Munawaroh; Eliyanto Eliyanto; Atim Rinawati; Sudadi Sudadi; Nginayatul Khasana; Siti Fatimah (Indonesian Journal of Innovation in Education Research, 2026)
This research aims to determine the extent of the influence of Psychological Tests and the Distance Traveled by Students on the Learning Outcomes of students at MIN 1 Kebumen and can classify them based on the results of psychological tests. The research conducted at MIN 1 Kebumen uses data collection techniques in the form of Psychological Tests and Learning Assessment with a quantitative approach. The sample consists of 113 students from the 1st grade of MIN 1 Kebumen, and the same number of students was selected as the sample. Data analysis technique using linear regression test with the assistance of SPSS Version 25.0 application. Research results indicate that: 1) there is no influence between psychological tests and learning outcomes; 2) there is an influence between travel distance and learning outcomes; 3) the magnitude of the influence of travel distance on learning outcomes is 3.39%.